An Integrated isotopic study of Early Intermediate Period camelid husbandry in the Santa Valley, Perú. (2nd July 2020) - Szpak, Paul; Millaire, Jean-François; Chapdelaine, Claude; White, Christine D.; Longstaffe, Fred J.
ABSTRACT: Stable carbon and nitrogen isotope compositions were determined for camelid bone collagen, hair, and wool (fibre) sampled from textiles from archaeological sites in the Santa Valley (north coast of Perú) occupied during Moche III (El Castillo, A.D. 300−500) and Moche IV (Guadalupito, A.D. 500−700) phases; a small number of camelid bone collagen samples were also analysed from the Late Suchimancillo Phase (A.D. 0−300). These data suggest that localised camelid husbandry was practiced in the Santa Valley from at least the Moche III phase. The nature of camelid husbandry likely involved animals being kept spatially segregated and fed a diverse range of fodder. The isotopic compositions of the bone collagen and wool textiles were very similar, which suggests that the wool that was used to produce the textiles was derived from local camelids rather than being acquired from the highlands. The transition from Moche III to Moche IV, which saw a significant increase in Mochica presence in the Santa Valley, was not accompanied by major changes in camelid husbandry practices. Localised camelid husbandry continued through this transition with minimal change; the prolonged droughts of the sixth century A.D. had no discernable effect on camelid husbandry, probably due to the special hydraulic conditions unique to the Santa Valley.